VD_FINDINFO HC / 2012 / 450 vom 16. Mai 2012 - VD Tribunal cantonal (2012)
RECTIFICATION DE LA DÉCISION, RECTIFICATIONEN GÉNÉRAL, ACTION EN RECTIFICATION, INTERPRÉTATIONSENS GÉNÉRAL | 334 al. 1 CPC (CH), 334 al. 3 CPC (CH), 334 CPC (CH)